Energy as the Mediator between Natural and Supernatural Realms - Kristel Kivari (Journal of Ethnology and Folkloristics)
This article discusses contemporary vernacular theory about the elusive energies that emanate from the ground. These energies are reported to be the ultimate reason for different remarkable occurrences, both natural and supernatural. The hypothesis of special energies is expressed in local tourism, in ecological debates and healing practises, driving the curiosity of amateur science. In these expressions knowledge as a form of engagement with the supernatural plays an integrating role between the individual and the forces beyond.